Impact of the UlÃ» Al- Ilm Model on Six Domains of Student Learning Outcomes in Islamic Religious Education - Budiyanti, Nurti; Komariah, Kokom St; Hermawan, Wawan; Jenuri, Jenuri; Hyangsewu, Pandu (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2024)
This study explores the application of the ulÃ» al-'ilm model, a Quranic learning approach, to enhance Islamic Religious Education (IRE). The purpose of the study is to examine its effectiveness in improving six crucial dimensions of student learning outcomes: cognitive, affective, psychomotor, ethical, social, and spiritual. Employing a quantitative experimental methodology with a pre-experimental design, specifically the one-group pretest-posttest approach, the research utilized statistical analysis through SPSS. The findings highlight the effectiveness of the ulÃ» al-'ilm model in advancing student learning outcomes. In the cognitive domain, there was a significant increase from 2.50% in the pretest to 40.00% in the post-test. A similar pattern emerged across the affective (16.25% to 43.75%), psychomotor (3.75% to 30%), social (11.25% to 35%), ethical (5.00% to 42.50%), and spiritual (2.50% to 71.25%) realms. The SPSS data supports the positive impact of the ulÃ» al-'ilm model on riyÃ¢á¸ah 'amaliyah, facilitated through coaching, example setting, habituation, appreciation, and repetition during the IRE learning process. This study underscores the multifaceted benefits of integrating the ulÃ» al-'ilm model in fostering comprehensive student development within the context of Islamic education.